(untitled) (Islas, 2026)
Introduction: This paper compares human translations of the cultural elements found in a German literary bestseller with the translations produced by the DeepL machine translation engine. The aim is to demonstrate the superiority of human translation over machine translation, the quality of which has recently been the subject of numerous studies. Methods: This study compares human translation with machine translation of the cultural elements found in a German bestseller that is heavily infused with these cultural references. It is a qualitative descriptive analysis of the first 50 pages of the book, building on previous research and drawing on various studies on the translation of cultural elements and the quality of neural machine translation engines. Results: The results produced by human translation and machine translation when rendering the cultural elements found throughout the novel under study differ significantly and confirm the initial hypothesis that machine translation fails to achieve a level of quality comparable to that of human translation when conveying cultural elements in literary works, especially in the case of a work with a deep humorous tone. Conclusions: The strong humorous and cultural elements present on the work under analysis require a series of interpretive strategies to adequately address most of the translation challenges it presents—strategies that machine translation lacks, as demonstrated by a close comparison of results across each of the cultural categories examined.